PENINGKATAN KEMAMPUAN KOSAKATA BAHASA JEPANG PADA KELAS BAHASA JEPANG TINGKAT MENENGAH MELALUI PENDEKATAN INTEGRATIF - Suyanti Natalia (Jurnal Ilmu dan Budaya, 2016)
In the field of language teaching, teachers or instructor are always looking approaches, methods and techniques which good to help students to more easily mastering the vocabulary in each subject, this makes me as a japanese language teacher trying to make a design using the technique as integrative teaching. In this paper described that teaching vocabulary using the theory of Paul Nation. A method described by H. Douglas Brown as a design which associate a language skill is intended that students memorize vocabulary more easily found in every lessons. This teaching method combines integrative teaching language skills such as listening, speaking, reading and writing in the design of teaching and apply it to the existing courses in Japanese language study program at the National University. In this paper, design attached are how to teach Japanese Grammar